PROTECTIVE EFFECTS OF DL-TRYPTOPHAN ON BENZIDINE-INDUCED HEPATIC TUMOR IN MICE - YOSHIDA, Osamu; MIYAKAWA, Mieko (GANN Japanese Journal of Cancer Research, 1980)
This study was undertaken to evaluate the carcinogenic effect of benzidine on the urinary bladder of mice, and the effect of DL-tryptophan on the induction of bladder cancer. Benzidine plus DL-tryptophan or benzidine alone mixed with a commercial basal diet was fed to groups of ICR strain female mice for 20 weeks, after a glass bead had been inserted into the bladder. Control mice were fed the basal diet throughout the experimental period. All the surviving mice were killed 63 weeks after start of the study. Benzidine administered with or without DL-tryptophan did not induce tumors of the urinary bladder in these mice. Hepatomas developed in 34 of 41 mice (82.9%) fed benzidine and in 24 of 51 mice (47.1 %) fed benzidine with tryptophan. DL-Tryptophan counteracted the effect of benzidine and significantly reduced the development of hepatomas.